2017
DOI: 10.3340/jkns.2017.0606.003
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Lumbar Interbody Fusion and <i>in Situ</i> Screw Fixation for Rostral Adjacent Segment Stenosis of the Lumbar Spine

Abstract: ObjectiveThe purpose of this study is to describe the detailed surgical technique and short-term clinical and radiological outcomes of lateral lumbar interbody fusion (LLIF) and in situ lateral screw fixation using a conventional minimally invasive screw fixation system (MISF) for revision surgery to treat rostral lumbar adjacent segment disease.MethodsThe medical and radiological records were retrospectively reviewed. The surgery was indicated in 10 consecutive patients with rostral adjacent segment stenosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This revision method can shorten the operation time and decrease bleeding. The radiological findings showed that the segmental angle and anterior disc height were significantly improved [14].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This revision method can shorten the operation time and decrease bleeding. The radiological findings showed that the segmental angle and anterior disc height were significantly improved [14].…”
Section: Discussionmentioning
confidence: 92%
“…Louie et al selected stand-alone LLIF to treat symptomatic ASD [13]. Choi et al reported that LLIF supplemented with lateral screw fixation was an alternative surgical option for ASD [14]. Segmental and regional lordosis, as well as intervertebral disc height, were improved and remained stable after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This revision method can shorten the operation time and decrease the bleeding. The radiological findings showed that the segmental angle and anterior disc height were significantly improved [12].…”
Section: Discussionmentioning
confidence: 92%
“…The reoperation choice is often quite diverse and now we lack some high-quality clinical proofs for superiority of any surgical treatment. Choi et al reported LLIF supplemented with lateral screw fixation is an alternative surgical option for ASD [12]. Louie et al selected stand-alone LLIF to treat symptomatic ASD [13].…”
Section: Introductionmentioning
confidence: 99%
“…4 Against this background, some surgeons suggested that the use of lumbar lateral interbody fusion may provide effective treatment of symptomatic ASD. 3,5,6 Here, we report three cases with symptomatic ASD after posterior fixation, which were salvaged by oblique lateral interbody fusion (OLIF) surgery.…”
Section: Introductionmentioning
confidence: 99%